An analysis of determiners error in English composition of the students of MAN 1 Kota Cirebon - Susilawati Susilawati; Niawati Niawati (Concept : Community Concern for English Pedagogy and Teaching, 2018)
This research attempts to investigate students’ common errors in using determiners and to find out the causes of students’ errors in their English writing. MAN 1 Kota Cirebon was used as the site for this research. The descriptive qualitative was used to be the research design of this research. The participants were 30 students. They were asked to write an English composition. In-depth interview was used to find out the causes of students’ errors. The result of the research shows that the common errors of the use of determiners are article with 39 cases (17.6%), followed by possessive 16 cases (7.2%), and quantifiers 6 cases (2.7%). The errors are caused by mother tongue inference, encouraged by teaching material and methods, false concept Hypothesized, and motivation. The writers find that mother tongue inference becomes the most common reason why the students made errors in their writings. However, they rarely find difficulties in applying possessive and quantifiers Key words: error analysis, determiner